Through a mother's lens: exploring maternal knowledge and skill acquisition in the in-person sessions of the Naungan Kasih positive parenting intervention in Malaysia - Mohd Nadzri, Farah Zeehan; Juhari, Rumaya; Kahar, Rojanah; Arshat, Zarinah; Madon, Zainal; Lachman, Jamie M (2025)
In Malaysia, there are significant worries about inadequate parenting practices and the mistreatment of children, especially in low to middle-income areas where parents often do not have access to helpful resources. Many mothers encounter difficulties in promoting positive child development, resulting in detrimental outcomes for children. The Naungan Kasih Positive Parenting Intervention was designed to address these gaps by equipping mothers with essential parenting skills and support. This pilot study investigates the experiences of 74 mothers who participated in the program across Selangor and Putrajaya, Malaysia. A qualitative descriptive approach was employed, collecting data one month post-intervention through three focus group discussions (FGDs) and nine in-depth interviews, targeting mothers with varied programme attendance levels. This approach enabled an understanding of how mothers incorporated program content into their parenting practices and perceptions of child development. The findings reveal that Naungan Kasih significantly impacted participating mothers, enhancing their confidence in parenting and decision-making. Mothers expressed gratitude for the knowledge and skills gained, noting that they felt more empowered and dedicated to their roles. The program’s supportive environment encouraged mothers to share experiences, challenges, and successes, fostering group learning and a sense of community. Many reported improvements in parent-child interactions and positive changes in their children's behavior, demonstrating the program's practical impact on family dynamics. Additionally, the study identified potential barriers to the program’s success, such as resource allocation and program duration, which are crucial for future implementation. The age-based weekly interventions were particularly effective, allowing mothers to engage with content relevant to their child’s developmental stage and share insights within the group. In conclusion, the Naungan Kasih Positive Parenting Programme shows significant potential in empowering mothers, fostering positive family relationships, and promoting healthier parenting practices. While the program's in-person approach and content delivery were well-received, considerations regarding program duration and resource availability should be addressed for broader scalability and long-term sustainability. This study offers valuable insights into the program’s effectiveness from a maternal perspective, highlighting its role in strengthening family dynamics.